Standardizing the clinical and dermatoscopic exam for patients with afro‐textured hair and scarring alopecia: A scoping review and clinical guide. Issue 1 (14th February 2022) - Adotama, Prince; Shapiro, Jerry; Lo Sicco, Kristen; London, Ashley O.; Ederaine, Sophia A.; Rotemberg, Veronica; Mayo, Tiffany
Abstract: Alopecia is one of the most common reasons for a dermatology visit among Black patients. Patients with concomitant afro‐textured hair and scarring alopecias are often subjected to delays in diagnosis and treatment. Race‐discordant physicians may find the examination of scarring alopecias in ethnic hair to be daunting. Herein we present a standardized approach to evaluating the hair and scalp in afro‐textured alopecia patients in the hopes of providing a framework and guide for the proper clinical assessment of these patients. This guide focuses on common scarring alopecias specific to this ethnic population including traction alopecia, central centrifugal alopecia, frontal fibrosing alopecia and lichen planopilaris.